INCREASED INCIDENCE OF PEPTIC ULCER DISEASE IN CENTRAL SEROUS CHORIORETINOPATHY PATIENTS: A Population-Based Retrospective Cohort Study. Issue 2 (February 2015) - Chen, San-Ni; Lian, Iebin; Chen, Yi-Chiao; Ho, Jau-Der
Abstract : Purpose: To investigate peptic ulcer disease and other possible risk factors in patients with central serous chorioretinopathy (CSR) using a population-based database. Methods: In this population-based retrospective cohort study, longitudinal data from the Taiwan National Health Insurance Research Database were analyzed. The study cohort comprised 835 patients with CSR and the control cohort comprised 4175 patients without CSR from January 2000 to December 2009. Conditional logistic regression was applied to examine the association of peptic ulcer disease and other possible risk factors for CSR, and stratified Cox regression models were applied to examine whether patients with CSR have an increased chance of peptic ulcer disease and hypertension development. Results: The identifiable risk factors for CSR included peptic ulcer disease (adjusted odd ratio: 1.39, P = 0.001) and higher monthly income (adjusted odd ratio: 1.30, P = 0.006). Patients with CSR also had a significantly higher chance of developing peptic ulcer disease after the diagnosis of CSR (adjusted odd ratio: 1.43, P = 0.009). Conclusion: Peptic ulcer disease and higher monthly income are independent risk factors for CSR. Whereas, patients with CSR also had increased risk for peptic ulcer development. Abstract : Supplemental Digital Content is Available in the Text.Peptic ulcer is a risk factor for central serous chorioretinopathy. Patients with central serous chorioretinopathy also have higher risk of developing peptic ulcer.